2021
DOI: 10.1186/s13072-021-00400-z
|View full text |Cite
|
Sign up to set email alerts
|

Losing DNA methylation at repetitive elements and breaking bad

Abstract: Background DNA methylation is an epigenetic chromatin mark that allows heterochromatin formation and gene silencing. It has a fundamental role in preserving genome stability (including chromosome stability) by controlling both gene expression and chromatin structure. Therefore, the onset of an incorrect pattern of DNA methylation is potentially dangerous for the cells. This is particularly important with respect to repetitive elements, which constitute the third of the human genome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 233 publications
3
60
0
Order By: Relevance
“…In general, an increase in genome methylation is associated more often with a decrease in the expression level as a result of tighter binding of methylated DNA to the nucleosome [51,52]. Nevertheless, some genes can avoid this and be hypomethylated during general hypermethylation, both in various diseases and during adaptation to extreme conditions [53][54][55], demonstrating a high level of expression against the background of transcriptional silencing, which may explain the high level of expression of ACTN1 in the described cases of endometriosis. For example, for alpha-actinin1 in the tissues of the heart, lungs, and testes under conditions of weightlessness simulation, it was shown that CpG islands in the promoter region avoid global methylation and the expression of ACTN1 in these cases increases [54].…”
Section: Discussionmentioning
confidence: 94%
“…In general, an increase in genome methylation is associated more often with a decrease in the expression level as a result of tighter binding of methylated DNA to the nucleosome [51,52]. Nevertheless, some genes can avoid this and be hypomethylated during general hypermethylation, both in various diseases and during adaptation to extreme conditions [53][54][55], demonstrating a high level of expression against the background of transcriptional silencing, which may explain the high level of expression of ACTN1 in the described cases of endometriosis. For example, for alpha-actinin1 in the tissues of the heart, lungs, and testes under conditions of weightlessness simulation, it was shown that CpG islands in the promoter region avoid global methylation and the expression of ACTN1 in these cases increases [54].…”
Section: Discussionmentioning
confidence: 94%
“…All of these changes could result in hypomethylation of certain loci and lasting imprints of infection. Hypomethylation may also induce genomic instability ( Pappalardo and Barra, 2021 ). We also observed down-regulation of several HDACs ( HDAC4 , 6, and 10) suggesting decreased histone deacetylation, which is essential for histone-DNA interaction.…”
Section: Discussionmentioning
confidence: 99%
“…This was also concordant with a previous study that revealed an association of haloperidol and increased global DNA methylation levels in leukocytes ( Melas et al, 2012 ). It should be noted that the possible role of intergenic DNA methylation is to repress the activity of harmful genetic elements such as transposons ( Pappalardo and Barra, 2021 ). DNA methylation of the gene body is also associated with altered gene expressions ( Moore et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%